Pengaruh Kualitas Produk dan Harga Pada Minat Beli terhadap Keputusan Pembelian Parfum Refill di Toko Inc.Redible - Frandhana, Adi; Ali, Hapzi (Siber Nusantara Publisher, 2024)
The research carried out aims to determine simultaneously and partially the independent variables, namely Product Quality and Purchase Interest, the dependent variables, namely Price and Purchase Decision. This research was conducted at the Perfume Refill INC Shop. Redible. The method used in this research is a quantitative method, where this research uses the Purposive Sampling technique using the Slovin formula to determine the sampling method. The population in this study were all consumers of the Perfume Refill Inc. Shop. Redible, totaling 90 respondents.Based on the research results, it shows that the variables Price and Product Quality on Purchasing Decisions provide a path coefficient value of 0.773 and have a p- value of 0.042 and a T-statistic value of 2.374 (T-statistic < T table 1.96). Shows that product quality influences purchasing decisions. Furthermore, the Price and Purchase Interest variables on Purchase Decisions provide a path coefficient value of 0.094 and have a p-value of 0.021 and a T-statistic value of 1.998 (T-statistic > T table 1.96). Shows that product quality influences purchasing decisions